Breeding Strategy of Local Muscovy to Support the Development of Meat Type Duck Industry - Triana Susanti (Indonesian Center for Animal Research and Development, 2021)
Muscovy duck is one of the genetic resources of waterfowl that spreads almost all over Indonesia. Muscovy duck is classified as meat-producer waterfowl, because of its relatively large body weight and better meat quality compared to other waterfowl. Therefore, cross breeding between Muscovy and ducks were often conducted by farmers to produce offspring with large body weight in order to anticipate the higher demand for duck meat. If this crossing pattern has been widely adopted by breeders, it will require a larger number of Muscovy duck. Whereas, currently the population of Muscovy is relatively low and no breeding system exists both at the community farm level or industrial level. Therefore, a development program of local Muscovy duck, especially its breeding program needs to be done immediately. As an information material to facilitate the preparation of the program, this paper describes factors that affect the breeding program including production performance and reproduction, as well as the breeding strategy of Muscovy duck as candidates of male line to form special type of meat type ducks through 3 groups of livestock breeds in the shape of a conical triangle at the top. The top position was the pure stock (nucleus), the middle was the parent stock (multiplier) and the bottom was the commercial stock. The genetic quality of livestock flows from the top position to the bottom and cannot be the other way around, because the breeding system is closed in the pure stock (nucleus).